2023
DOI: 10.1001/jamanetworkopen.2022.54157
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cancer Predisposition Syndromes in a National Cohort of Children With a Neoplasm

Abstract: ImportanceTo improve diagnostics of cancer predisposition syndromes (CPSs) in children with cancer, it is essential to evaluate the effect of CPS gene sequencing among all children with cancer and compare it with genetic testing based on clinical selection. However, a reliable comparison is difficult because recent reports on a phenotype-first approach in large, unselected childhood cancer cohorts are lacking.ObjectiveTo describe a national children’s cancer center’s experience in diagnosing CPSs before introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Studies that did find an increased risk of cancer in first degree relatives of children with cancer noted that there may be an interplay between genetic susceptibility and environmental factors in the etiology of tumors, but that hereditary cancer syndromes could not entirely account for this increased risk. Indeed, recent studies indicate that the rates of children with cancer considered to have an underlying cancer predisposition may be higher than previously thought, reaching approximately 10% 34–36 . However, this prediction is limited by the fact that this is a rapidly evolving field as the numbers of recognized cancer predisposition genes and syndromes, as well as imaging and laboratory techniques to identify these genes are constantly growing and improving 34–36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that did find an increased risk of cancer in first degree relatives of children with cancer noted that there may be an interplay between genetic susceptibility and environmental factors in the etiology of tumors, but that hereditary cancer syndromes could not entirely account for this increased risk. Indeed, recent studies indicate that the rates of children with cancer considered to have an underlying cancer predisposition may be higher than previously thought, reaching approximately 10% 34–36 . However, this prediction is limited by the fact that this is a rapidly evolving field as the numbers of recognized cancer predisposition genes and syndromes, as well as imaging and laboratory techniques to identify these genes are constantly growing and improving 34–36 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies indicate that the rates of children with cancer considered to have an underlying cancer predisposition may be higher than previously thought, reaching approximately 10%. [34][35][36] However, this prediction is limited by the fact that this is a rapidly evolving field as the numbers of recognized cancer predisposition genes and syndromes, as well as imaging and laboratory techniques to identify these genes are constantly growing and improving. [34][35][36] In our exposed mothers cohort, the three most common cancer diagnoses were breast (36.6%), thyroid (12.2%), and gastrointestinal (11.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimizing the risk of adverse events, with the development of another metachronous cancer as one of the most important side effects, can improve healthcare delivery [31][32][33]. Very often, patients with CPSs are at higher risk of developing several cancers, not just one type [1,16], so preventive management is essential to avoid increasing the already elevated risk of cancer in these cases. The question "How should we guide treatment?"…”
Section: Genementioning
confidence: 99%
“…A recent retrospective study of a phenotype-first approach for ChiCaP diagnostics demonstrated a diagnostic yield of 8.6%. 11 However, phenotype-first approaches require robust clinical screening tools to identify patients with ChiCaP syndromes. 12 …”
Section: Introductionmentioning
confidence: 99%